NMR detection of chirality and enantiopurity of amines by using benzene tricarboxamide-based hydrogelators as chiral solvating agents. (2nd August 2016) - Jung, Sung Ho; Kim, Ka Young; Ahn, Ahreum; Lee, Shim Sung; Choi, Myong Yong; Jaworski, Justyn; Jung, Jong Hwa
Abstract : The use of gelator1D as a means for NMR-based determination of the enantiopurity and chirality of amines. Abstract : Enantiomeric excess of chiral compounds is a key parameter that can influence their activity or therapeutic action. Current approaches to the rapid measurement of enantiomeric excess using 1 H NMR is based on the formation of diastereomeric complexes between chiral analytes and a chiral host, leading to two species with no symmetry relationship. Here, we demonstrate that a gelator host system can provide a means to elicit distinct chemical shifts in the 1 H nuclear magnetic resonance (NMR) of a mixture of diamines or monoamines depending on the corresponding enantiomeric excess of the guest mixture of chiral amines. These gelator hosts provide a unique example of NMR based assessment of the chirality and enantiopurity of guest amines.